Anger of images: control, resistance, war - Arçari, André; Zorzal, Bruno (Farol, 2024)
We recognize that an image is never unique, but always multiple, and its meanings are only revealed in the chain of relationships to which it is part based on careful views. In the arts of moving images, we can mention the multiplicity of cinema and video fields. At its dawn, analog cinema, as we know, constituted movement by illusion, through a succession of frames chained one next to the other, or above and below, if we look at a celluloid film vertically, to then suggest the location of bodies and the constituent elements of the scenes. In view of this, photographic and filmic seeing were modulated in a relationship of capture and montage. Whether by capturing images and then assembling them in successive shots or dismantling pre-existing images to later reassemble them with the intention of giving them a new vitality, a new body to belong to.